Enhancing immunogenic responses through CDK4/6 and HIF2α inhibition in Merkel cell carcinoma - Lee, Jung Hyun; Lee, Justin Daho; Paulson, Kelly; Voillet, Valentin; Berndt, Andre; Church, Candice; Lachance, Kristina; Park, Song Y.; Yamamoto, Naomi K.; Cromwell, Elizabeth A.; Gottardo, Raphael; Chapuis, Aude G.; et al. (Heliyon, 2024)
Approximately 50% of Merkel cell carcinoma (MCC) patients facing this highly aggressive skin cancer initially respond positively to PD-1-based immunotherapy. Nevertheless, the recurrence of MCC post-immunotherapy emphasizes the pressing need for more effective treatments. Recent research has highlighted Cyclin-dependent kinases 4 and 6 (CDK4/6) as pivotal cell cycle regulators gaining prominence in cancer studies. This study reveals that the CDK4/6 inhibitor, palbociclib can enhance PD-L1 gene transcription and surface expression in MCC cells by activating HIF2α. Inhibiting HIF2α with TC-S7009 effectively counteracts palbociclib-induced PD-L1 transcription and significantly intensifies cell death in MCC. Simultaneously, co-targeting CDK4/6 and HIF2α boosts ROS levels while suppressing SLC7A11, a key regulator of cellular redox balance, promoting ferroptosis- a form of immunogenic cell death linked to iron. Considering the rising importance of immunogenic cell death in immunotherapy, this strategy holds promise for improving future MCC treatments, markedly increasing immunogenic cell death across various MCC cell lines, thus advancing cancer immunotherapy.